The Invasion and Encapsulation of the Entomopathogenic Nematode, Steinernema abbasi, in Aedes albopictus (Diptera: Culicidae) Larvae - Liu, Wei-Ting; Chen, Tien-Lai; Hou, Roger F.; Chen, Cheng-Chen; Tu, Wu-Chun (Insects (Basel, Switzerland), 2020)
The Asian tiger mosquito, Aedes albopictus, is of crucial concern to the public and veterinary health because of its vector role in transmission of several mosquito-borne diseases. Over the past decades, entomopathogenic nematodes (EPNs) have been used to control important agricultural insect pests and are considered to be effective against mosquitoes as well. The objectives of this study were to investigate the mosquitocidal effects of Steinernema abbasi to Ae. albopictus and the encapsulation processes of invading nematodes in the mosquito host. In this study, we found that S. abbasi was pathogenic to 3rd and 4th instar larvae of Ae. albopictus by entering the hemocoel of the 3rd and 4th instar larvae mainly through mouth and gastric caecum or by penetrating pupae through the intersegmental membrane or trumpet. The mosquito larvae infected with a single nematode caused a high mortality. Although EPNs in the hemocoel of mosquitoes were melanized and encapsulated, most Ae. albopictus larvae failed to survive after infection with S. abbasi. Overall, we demonstrated that S. abbasi is pathogenic to Ae. albopictus larvae, suggesting that this S. abbasi isolate has potential as a biocontrol agent for managing this vector mosquito.